Archie. two worlds, two loves, two destinies - Kupperberg, Paul (Archie Comic Publications, 2013)
"Find out what happens after the 'I do's'! Delve deeper into all of the emotion and drama. Last time, Reggie was on trial for extortion, Moose settled in as mayor, and Archie & Betty became teachers at Riverdale High. This time, a hero returns to Riverdale to tie the knot, while Veronica continues her downward spiral and Archie has finally had enough!" -- p. [4] of cover.